GERAKAN “SATU RUMAH SATU MASKER”: EDUKASI ETIKA BATUK DAN PENATAAN VENTILASI ALAMI UNTUK PENCEGAHAN TB DI KECAMATAN GUNUNG MERIAH KABUPATEN DELI SERDANG - Novrika Silalahi; Pitto Pratiwi Malau; Rizka Annisa (INSTITUT KESEHATAN DELI HUSADA, 2026)
Tuberculosis (TB) remains a public health problem that requires family- and environment-based prevention efforts. This community service activity aimed to improve the knowledge and awareness of TB patients regarding cough etiquette, mask use, and the arrangement of natural ventilation through the “One House, One Mask” movement. The activity was conducted on February 10–11, 2026, in Gunung Meriah District, Deli Serdang Regency, involving 50 respondents with TB. The implementation methods included health education, demonstrations, discussions, mentoring, and evaluation through pre-test and post-test. The results showed that 42 respondents (84%) understood and were able to correctly practice cough etiquette, 44 respondents (88%) understood the importance of wearing masks in the household, and 39 respondents (78%) understood the importance of healthy natural ventilation. In addition, there was an average increase of 24% in knowledge scores based on the pre-test and post-test results. Active participation reached 46 respondents (92%), while 41 respondents (82%) expressed willingness to apply TB prevention behaviors in their households. This activity was effective in improving respondents’ knowledge, awareness, and participation in efforts to prevent TB transmission.